2023
DOI: 10.1108/rjta-12-2022-0159
|View full text |Cite
|
Sign up to set email alerts
|

Role of top management green commitment, adaptability culture and green product innovation in boosting organizational green performance in Pakistan

Abstract: Purpose Top management and managers must highlight environmental issues and adopt green product innovation (GPI) to implement eco-friendly management in their businesses. This research aims to examine the impact of top management’s green commitment and adaptability culture (AC) on organizational green performance (OGP) mediated by GPI. Design/methodology/approach The study was conducted in the context of the textile industry of Pakistan, where a sample of 232 employees was collected for the data analysis. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 97 publications
1
5
0
Order By: Relevance
“…In addition, Baah et al (2023) also revealed that green creativity was a pivotal precursor to green competitive advantage and financial performance in the manufacturing SME sector. Notwithstanding, our finding supports Gull et al's (2023) argument that organisations' green performance depends on top management's green commitment and adaptability to corporate culture. This meant that employees' green creative behaviour could be expected for green corporate performance in context, though further inquiry will be required.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…In addition, Baah et al (2023) also revealed that green creativity was a pivotal precursor to green competitive advantage and financial performance in the manufacturing SME sector. Notwithstanding, our finding supports Gull et al's (2023) argument that organisations' green performance depends on top management's green commitment and adaptability to corporate culture. This meant that employees' green creative behaviour could be expected for green corporate performance in context, though further inquiry will be required.…”
Section: Discussionsupporting
confidence: 84%
“…New technology implementation and green corporate performance Adopting new technologies is essential for achieving green business success and ties a company's green innovation to achieving green marketing performance (Nuryakin and Maryati, 2022;Jiang et al, 2020). Gull et al (2023) emphasised the need for top management and managers to implement green product innovation (GPI) initiatives. Gull et al (2023) established that organisations' green performance depended on top management's green commitment and adaptability to corporate culture.…”
Section: Hypotheses Development Green Communication Green Strategy Al...mentioning
confidence: 99%
See 3 more Smart Citations